INDUKSI TEKNOLOGI PENJUALAN ONLINE PADA PELANGI RASA KARANGLO POLANHARJO KLATEN - Purwanto, Eko (Bengawan : Jurnal Pengabdian Masyarakat, 2024)
This activity aims to introduce online sales technology as a sales strategy for Pelangi Rasa Small and Medium Enterprises, Karanglo Polanharjo Village, Klaten. The application package that will be applied to partners is an online sales application. The team will conduct training on marketing strategies through online sales for the sustainability of Pelangi Rasa Small and Medium Enterprises. This activity targets expanding marketing locations through online product sales. Technology induction activities are carried out in five stages, namely (1) Material preparation, (2) Training, (3) Equipment preparation, system configuration and system implementation, (4) Mentoring, and (5) Monitoring. At the material preparation stage, the team will compile a module, namely the use of online sales applications. The module creation will be equipped with presentation material that will be used in training sessions. The training stage uses discussion and demonstration methods so that partners can easily understand the material presented. This stage will concentrate on the introduction of online sales technology as a sales marketing strategy. In the equipment preparation, system configuration, and program implementation stages, the team and partners will work together to prepare equipment in the form of hardware and software. Partners, accompanied by the service team, will carry out the system configuration. Partners, with assistance from the service team, will carry out the program implementation process, which consists of implementing online sales applications. The service team will carry out the monitoring stage periodically and continuously. In the initial stage, monitoring will be carried out once a week to see the partners' progress in implementing the program. Furthermore, monitoring will be carried out once a month to see the impact of program implementation on partners regarding online sales at Pelangi Rasa Small and Medium Enterprises.